Oncologic treatment support via a dedicated mobile app: a prospective feasibility evaluation (OPTIMISE-1) - Schunn, Fabian; El-Shafie, Rami; Kronsteiner, Dorothea; Sauer, Lukas; Kudak, Andreas; Bougatf, Nina; Oetzel, Dieter; Krämer, Anna; Regnery, Sebastian; Machmer, Timo; Debus, Jürgen; Nicolay, Nils (Strahlentherapie und Onkologie, 2023)
Mobile health (mhealth) is gaining interest, with mobile devices and apps being ever more available among medical facilities and patients. However, in the field of radiation oncology, the medical benefits of mhealth apps are still underexplored. As an additional approach to patient care during radiotherapy, we designed a mobile treatment surveillance app based on patient-reported outcomes.